FACTORS AFFECTING THE WELFARE LEVEL OF RICE FARMERS IN KLAMBIR V KEBUN VILLAGE - Fadlan, Ahmad; Lubis, Rizal P.; Tarigan, Muhammad Handoko (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study purposed to empirically prove that land area, production, prices, education, labor, capital, government policies, and technology as factors influencing farmers' welfare. The SPSS program was utilized to illustrate the Path Method Analysis in the present research. The study's participants were all Klambir V Kebun village farmers. 226 respondents who were rice farmers made up the study's sample. Data for this study were gathered by questionnaires, documentation, interviews, and observation. The findings proved that three factors—the land area factor, the capital factor, and the pricing factor—were found out of the eight variables investigated through factor analysis. Simultaneously, land area, capital, and price significantly influenced the welfare of rice farmers in Klambir V Kebun Village, Hamparan Perak Subdistrict, Deli Serdang Regency. There needs to be a market that provides agricultural needs, such as fertilizers, seeds, pesticides and others, both before the planting season and during the harvest season. There is a need for transportation of paddy buyers during the harvest process so that farmers do not have to incur transportation costs to deliver the harvest to the buyer.  Government policy that can help farmers is to prioritize farmers' crops over imported rice, so that it can make farmers' income increase